2006
DOI: 10.1111/j.1525-1497.2005.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction with a single general self-rated health question

Abstract: Objective: Health planners and policy makers are increasingly asking for a feasible method to identify vulnerable persons with the greatest health needs. We conducted a systematic review of the association between a single item assessing general self‐rated health (GSRH) and mortality. Data Sources: Systematic MEDLINE and EMBASE database searches for studies published from January 1966 to September 2003. Review Methods: Two investigators independently searched English language prospective, community‐based co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
1,460
3
43

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,928 publications
(1,602 citation statements)
references
References 45 publications
44
1,460
3
43
Order By: Relevance
“…Fonte: Pesquisa Nacional por Amostra de Domicílios, Instituto Brasileiro de Geografi a e Estatística RP ajustada por sexo e IC95% estimados por regressão de Poisson indicadores mais utilizados em inquéritos populacionais devido à simplicidade de obtenção da informação e ao seu valor prognóstico para a mortalidade e a capacidade funcional. 4,8,13 Além disso, ela é uma medida multidimensional que expressa as condições de saúde física e mental, os comportamentos em saúde e o bem-estar social. 8 Entretanto, há controvérsia quanto ao seu uso em pesquisas sobre desigualdades sociais.…”
Section: Métodosunclassified
“…Fonte: Pesquisa Nacional por Amostra de Domicílios, Instituto Brasileiro de Geografi a e Estatística RP ajustada por sexo e IC95% estimados por regressão de Poisson indicadores mais utilizados em inquéritos populacionais devido à simplicidade de obtenção da informação e ao seu valor prognóstico para a mortalidade e a capacidade funcional. 4,8,13 Além disso, ela é uma medida multidimensional que expressa as condições de saúde física e mental, os comportamentos em saúde e o bem-estar social. 8 Entretanto, há controvérsia quanto ao seu uso em pesquisas sobre desigualdades sociais.…”
Section: Métodosunclassified
“…Self-rated health (SRH) based on a single question asking people to rate their overall health status has been shown to be a reliable measure of individuals' subjective health, and is associated with both morbidity and mortality (DeSalvo et al 2006;Idler and Benyamini 1997;Kaplan et al 1996;Nielsen et al 2008;Singh-Manoux et al 2007). The mechanisms behind this association are not fully known.…”
Section: Introductionmentioning
confidence: 99%
“…21 A meta-analysis has shown that a single item assessing general self-rated health can accurately predict overall mortality. 22 We used self-reported health status and 15-year vital status data to estimate the risk of other-cause mortality among a population-based cohort of men with localized prostate cancer. We created a nomogram incorporating self-reported health status, age, and race/ethnicity to estimate other-cause mortality at 10 and 15 years after diagnosis.…”
mentioning
confidence: 99%